PENGUATAN MEMBACA KITAB KUNING MENGGUNAKAN METODE BITHAQATIL JUMAL PADA PESANTREN MU’ALLIMIN MUHAMMADIYYAH SAWAH DANGKA KAB. AGAM, SUMATERA BARAT - Adlan Sanur Tarihoran; Muhamad Rezi (Turast: Jurnal Penelitian dan Pengabdian, 2021)
One of the great traditions in Islamic education institutions in Indonesia is teaching by transmitting Islamic values as found in classical books written centuries ago. The majority in Indonesia, the classic book is better known as the Kitab Kuning. Teaching with the Kitab Kuning is usually done in Islamic Boarding Schools. Examining Kitab Kuning requires qualified Arabic language skills at least passively. Unfortunately, not all Islamic boarding schools that have a variety of superior programs in certain fields, are weak in the field of studying Kitab Kuning. One of them is the Islamic Boarding School Mu'allimin Muhammadiyyah Sawah Dangka which has the flagship Tahfizh Alquran program but is weak in the study of Kitab Kuning. One of the main factors is the lack of adequate quality of human resources. For this reason, this community service activity aims to provide training while introducing new, lightweight methods in learning Arabic, namely the Bihaqatil Jumal method. This method emphasizes learning Arabic using the right brain. After a series of community service activities, teachers and Islamic boarding schools felt helped and gained new experiences in learning Arabic methods to study Kitab Kuning. In addition, both the assisted object and the resource person requested that this kind of community service be continued.